SISTEM INFORMASI PUNISHMENT AND REWARD SERTA SMS GATEWAY DI SMP. NURUL JADID - Moh. Jasri; Ahmad Muzanni (Jurnal Teknologi Informasi dan Terapan, 2019)
The existence of information system which enables documenting of violation, achievement, and report for parents in importantly needed to monitor students’ progress. Therefore, the purpose of this research is to make Information System of Punishment, Reward, SMS Gateway in Nurul Jadid Junior High School for producing software of information system which can be used by Discipline Department in Nurul Jadid Junior High School to encode or produce report forparents about violations or students’ achievement. The method used in this research is qualitative method while the system of development method is waterfall method. The result of this research is a software examined for user applicant and fulfilling the standard based on patterned necessity analysis. By making Information System of Punishment, Reward, SMS Gateway in Nurul Jadid Junior High School which gives exact result and agrees with institution’s desire in problems of violation point recording, students’ achievement, and also report for parents is expected for developers to develop this information system by increasing student progress graphic or students’ accepted sanction kinds, while for user applicants, it is also expected to join training of made system use.